Enabling Factor Dominance in Women Farmer Group Participation: Time Availability and Production Resource Access - Ivana Nastia Az Zahra; Siwitri Munambar; Endah Puspitojati (Integrated Science Education Journal, 2026)
Purpose of the study: This study analyzed the simultaneous and partial influences of seven internal and external factors: age, education level, motivation, time availability, family support, access to production resources, and group management. Methodology: A census-based quantitative survey enrolled all 40 KWT members as respondents. Structured Likert-scale (1–5) questionnaires were administered and validated through item-total correlation analysis (r-critical = 0.312) and Cronbach's alpha reliability testing (α = 0.897). Ordinal data were transformed to an interval scale using the Method of Successive Intervals (MSI). Data were analyzed using multiple linear regression in SPSS v.25, preceded by normality (Kolmogorov–Smirnov), multicollinearity (VIF), heteroscedasticity (Glejser), and autocorrelation (Durbin–Watson) assumption tests at α = 0.05. Main Findings: All seven variables simultaneously and significantly influenced member participation (F = 11.002; p = 0.000; R² = 70.6%). Partial analysis confirmed that only time availability (β = 0.361; p = 0.005) and production resource access (β = 0.430; p = 0.007) were significant predictors, with production resource access being the strongest. Age, education level, motivation, family support, and group management showed no significant partial effects, with group management exhibiting a negative coefficient attributable to the free-rider effect. Novelty/Originality of this study: This study empirically demonstrates that enabling factors, time availability, and access to production resources dominate psychological, demographic, and managerial factors in determining actual KWT member participation. It simultaneously tests seven internal and external variables in a food-production-based empowerment context, reveals the intention-behavior gap mechanism, and proposes a structural-barrier-reduction framework for empowering agricultural women’s groups.